Three-dimensional simulation for fast forward flight of a calliope hummingbird. Issue 6 (June 2016) - Song, Jialei; Tobalske, Bret W.; Powers, Donald R.; Hedrick, Tyson L.; Luo, Haoxiang
Abstract : We present a computational study of flapping-wing aerodynamics of a calliope hummingbird ( Selasphorus calliope ) during fast forward flight. Three-dimensional wing kinematics were incorporated into the model by extracting time-dependent wing position from high-speed videos of the bird flying in a wind tunnel at 8.3 m s −1 . The advance ratio, i.e. the ratio between flight speed and average wingtip speed, is around one. An immersed-boundary method was used to simulate flow around the wings and bird body. The result shows that both downstroke and upstroke in a wingbeat cycle produce significant thrust for the bird to overcome drag on the body, and such thrust production comes at price of negative lift induced during upstroke. This feature might be shared with bats, while being distinct from insects and other birds, including closely related swifts.